Token Economy Intervention for Early Childhood Children with Attention Deficit and Hyperactivity Disorder - Novita Sari (Universitas Negeri Semarang, 2024)
This study describes the application of token economy intervention to an early childhood who has attention deficit disorder with hyperactivity. The method used is a qualitative case study, which involves in-depth observation and interviews with the child's parents and teachers. The research subject was a 5-year-old child who had difficulty in focusing attention accompanied by hyperactivity. The intervention was conducted for 23 days, during which the child was given tokens as rewards for positive behavior and certain achievements. The success of the intervention was measured by recording changes in the child's behavior. Interview techniques were also conducted to evaluate parents and teachers perceptions and provide education in helping to deal with children's problems. The results of the study showed a significant improvement in the child's ability to focus attention, this can be seen from the decrease in impulsive behavior and the increase in tasks that can be completed. In addition, parents reported positive changes in their child's daily interactions. The conclusion of this study is that token economy intervention can have a significant impact in improving the attention of early childhood with attention deficit disorder accompanied by hyperactivity, as well as providing insights for intervention practices in educational settings.